1995
DOI: 10.1080/00140139508925280
|View full text |Cite
|
Sign up to set email alerts
|

Computer mouse use and cumulative trauma disorders of the upper extremities

Abstract: The computer mouse is now present in virtually every office environment because of the recent adoption of the graphical user interface. However, Karlqvist et al. (1994) pointed out that there still remains a paucity of work on the musculoskeletal problems associated specifically with computer mouse use. Likewise, there have been no published data on the magnitude of upper extremity musculoskeletal disorders associated with computer mouse use. In order to ascertain this magnitude, claims data from the Liberty M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(34 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…There are indications that UEMSDs are related to computer work (Fogleman and Brogmus 1995, Karlqvist et al 1996, Punnett and Bergqvist 1997, Jensen et al 2002. In a few studies mouse use is indicated as a risk factor in computer work (Karlqvist et al 1996, 2002.…”
Section: Introductionmentioning
confidence: 99%
“…There are indications that UEMSDs are related to computer work (Fogleman and Brogmus 1995, Karlqvist et al 1996, Punnett and Bergqvist 1997, Jensen et al 2002. In a few studies mouse use is indicated as a risk factor in computer work (Karlqvist et al 1996, 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of the mouse has increased significantly during the last decade, little is known regarding the impact of its use on the musculoskeletal system. However, some studies indicate increased musculoskeletal symptoms in relation to mouse use (7,8).…”
mentioning
confidence: 99%
“…In modern society the number of employees involved in computer work increases (I), and there are indications that musculoskeletal disorders are associated with computer work (2)(3)(4)(5)(6). A study of technicians [computer-aided design (CAD) operators] working intensively with a computer mouse or mouse-like input devices, such as a puck, showed that computer work was performed in constrained postures with repetitive movements of the upper arm, the wrist, and the fingers and that the load on the shoulder and forearm muscles was low but static (2).…”
mentioning
confidence: 99%